Identifying the symptom and functional domains in patients with fibromyalgia: results of a cross-sectional Internet-based survey in Italy - Salaffi F; Mozzani F; Draghessi A; Atzeni F; Catellani R; Ciapetti A; Di Carlo M; Sarzi-Puttini P (Journal of Pain Research, 2016)
Fausto Salaffi,1 Flavio Mozzani,2 Antonella Draghessi,1 Fabiola Atzeni,3 Rosita Catellani,2 Alessandro Ciapetti,4 Marco Di Carlo,1 Piercarlo Sarzi-Puttini5 1Rheumatology Department, Polytechnic University of Marche, Jesi (Ancona), 2Department of Internal Medicine and Rheumatology, University Hospital of Parma, Parma, 3IRCCS Galeazzi Orthopedic Department, Milan, Italy; 4Rheumatology Department, Betsi Cadwaladr University Health Board, Glan Clwyd Hospital, Bodelwyddan, Denbighshire, Wales; 5Rheumatology Department, L. Sacco University Hospital, Milan, Italy Objective: The aims of this cross-sectional study were to investigate the usefulness of using an Internet survey of patients with fibromyalgia in order to obtain information concerning symptoms and functionality and identify clusters of clinical features that can distinguish patient subsets. Methods: An Internet website has been used to collect data. Fibromyalgia Impact Questionnaire Revised version, self-administered Fibromyalgia Activity Score, and Self-Administered Pain Scale were used as questionnaires. Hierarchical agglomerative clustering was applied to the data obtained in order to identify symptoms and functional-based subgroups. Results: Three hundred and fifty-three patients completed the study (85.3% women). The highest scored items were those related to sleep quality, fatigue/energy, pain, stiffness, degree of tenderness, balance problems, and environmental sensitivity. A high proportion of patients reported pain in the neck (81.4%), upper back (70.1%), and lower back (83.2%). A three-cluster solution best fitted the data. The variables were significantly different (P<0.0001) among the three clusters: cluster 1 (117 patients) reflected the lowest average scores across all symptoms, cluster 3 (116 patients) the highest scores, and cluster 2 (120 patients) captured moderate symptom levels, with low depression and anxiety. Conclusion: Three subgroups of fibromyalgia samples in a large cohort of patients have been identified by using an Internet survey. This approach could provide rationale to support the study of individualized clinical evaluation and may be used to identify optimal treatment strategies. Keywords: fibromyalgia, Internet, FIQR, FAS, cluster analysis, SAPS, pain